Basal-bolus insulin therapy in postoperative inpatients with diabetes mellitus: directions for future quality-improvement initiatives. (25th October 2017) - Cook, Curtiss B; Apsey, Heidi A; Glasgow, Amy E; Castro, Janna C; Habermann, Elizabeth B; Schlinkert, Richard T
Aim: To determine variables associated with hyperglycemia and insulin therapy in postoperative inpatients with diabetes mellitus following a quality-improvement initiative.Materials & methods: Patients with diabetes mellitus following an elective surgical procedure (n = 782; 877 surgical procedures) were selected.Results: Age, hemoglobin A1c corticosteroids, insulin therapy and year of surgery were associated (p < 0.01) with hyperglycemia. Hemoglobin A1c, hyperglycemia, case mix index and corticosteroids were associated (p ≤ 0.03) with insulin therapy. Hyperglycemia and use of insulin varied by surgical specialty.Conclusion: Data could be used to modify current treatment algorithms. Variations in hyperglycemia and insulin use by surgical specialty require further investigation. Lay abstract: It is important to control blood sugar levels in the hospital in patients who have had surgery. We found that certain characteristics such as hemoglobin A1c, disease complexity, frequency of high sugar measurements and use of steroids predicted the need for insulin. We also found that insulin was provided inconsistently across surgical specialties. These findings from this analysis could be used to develop uniform therapy to improve outcomes for surgical patients with diabetes mellitus.